The use of a diagram of the skull in the localization of pain - Silva Neto, Raimundo Pereira da (Headache Medicine, 2011)
The localization of the headache is important semiological dada, therefore this information it is useful in the knowledge of the etiology and of the distinguishing diagnosis, beyond influencing in the therapeutic option. The objective of the present study is to present a model of diagram of the skull, where the patient locates with exactness its pain. The simple descriptive register of the region of the skull that aches is not enough. When a diagram of the skull is presented the patient, the informations are more necessary and increase the accuracy of the diagnosis.